Polymer electrolyte liquid crystal system for improved optical and electrical properties. (May 2015) - Said, Suhana Mohd; Zulkifli, Ahmad Zulazlan Shah; Kamarudin, Muhammad Akmal; Mainal, Azizah; Subramanian, Balamurugan; Mohamed, Nor Sabirin
Graphical abstract: Highlights: A polymer electrolyte mixture doped with liquid crystal mixture was prepared. The liquid crystal droplets are embedded inside the polymer network. Electrical conductivity of the mixture was correlated with the liquid crystal phase. The presence of liquid crystal act as a pathway for the ionic movement. Improvement in electrochemical and optical band gap was achieved. Abstract: Polymer electrolytes are electrolytes that consist of polymer/salt complex and contain free ions which render them electrically conductive. They are used extensively in applications such as batteries, capacitors, and photovoltaic cells. In this study, a series of 4-cyano-4′-pentylbiphenyl (5CB) nematic liquid crystal-doped polyvinyl alcohol (PVA) polymer electrolytes were prepared and the effects of the concentration of the doped 5CB on the properties of the electrolytes were characterized by alternating current (AC) impedance spectroscopy. The increase in conductivity which was achieved through the doping of 5CB suggests that the embedded liquid crystal (LC) molecules increased the ordering strength in the electrolyte, which provides a better pathway to transfer generated charges inside the polymer electrolyte. Characterization of the polymer electrolyte liquid crystal system (PeLCs) by electrochemical and spectroscopic techniques reveals the influence of LC in the PeLC optical and electrochemical band gaps.